The role of blockchain and corporate governance in financial reporting quality- a systematic literature review - Ayu Kunariyah; Totok Dewayanto (Jurnal Akademi Akuntansi)
Purpose: This study aims to explore the role of blockchain and corporate governance in enhancing financial reporting quality using a Systematic Literature Review (SLR) approach.